A Comparative Analysis of Yield Gaps and Water Productivity on Smallholder Farms in Ethiopia, South Africa and Tunisia. (30th March 2018) - Jovanovic, Nebo; Musvoto, Constansia; De Clercq, Willem; Pienaar, Cou; Petja, Brilliant; Zairi, Abdelaziz; Hanafi, Salia; Ajmi, Tarek; Mailhol, Jean Claude; Cheviron, Bruno; Albasha, Rami; Habtu, Solomon; et al.
Abstract: Agriculture in developing countries will have to transform and increase production by an estimated 70% in order to meet demands by 2050. Although well‐managed commercial farms offer little manoeuvring space for increasing agricultural water productivity, smallholder farms usually operate at low input costs and therefore provide ample opportunities to reduce the potential yield gap through agricultural intensification. The aim of this paper is to analyse and compare yields and water productivities obtained in field and modelling experiments in Ethiopia (maize, garlic, onion), South Africa (tomato) and Tunisia (tomato, potato, wheat). Innovative agricultural practices were introduced on smallholder farms: irrigation scheduling and NPS Zn fertilization in Ethiopia; high‐yielding cultivar, drip irrigation, mulching and organic amendments in South Africa; and crop water modelling in Tunisia. In general, crop yields increased up to eight times with innovative practices compared to current conventional farming practices. Crop water productivities were fairly stable within the same experiments, but increased with innovations, indicating that intensive farming can be more environmentally sustainable than conventional farming. Intensive farming systems in a resource‐rich environment (high radiation levels, relatively fertile, deep and well‐drained soils), combined with technology transfer and capacity building could be seen as viable strategies to secure food for smallholders and communities in African rural areas, as well as to improve water utilization in water‐scarce catchments. Copyright © 2018 John Wiley & Sons, Ltd. Résumé: L'agriculture des pays en développement devra transformer et augmenter sa production d'environ 70% afin de répondre aux besoins d'ici à 2050. Si les fermes commerciales bien gérées offrent peu d'espace de manœuvre pour accroître la productivité de l'eau agricole, a contrario, les petites exploitations fonctionnent généralement à faible coût des intrants et offrent donc de nombreuses possibilités de réduire l'écart de rendement potentiel par l'intensification de l'agriculture. Le but de cet article est d'analyser et de comparer les rendements et les productivités d'eau obtenus dans des expériences de terrain et de modélisation en Ethiopie (maïs, ail, oignon), en Afrique du Sud (tomate) et en Tunisie (tomate, pomme de terre, blé). Des pratiques agricoles innovatrices ont été introduites dans les petites exploitations: l'irrigation et la fertilisation du NPS Zn en Ethiopie, l'irrigation par goutte‐à‐goutte, le paillage et les amendements organiques en Afrique du Sud, et la modélisation des cultures et de l'eau en Tunisie. En général, le rendement des cultures a augmenté jusqu'à huit fois avec des pratiques innovantes par rapport aux pratiques agricoles classiques actuelles. De même, la productivité de l'eau cultivée a augmenté avec les innovations, indiquant que l'agriculture intensive peut être plus écologiquement durable que l'agriculture conventionnelle. Les systèmes agricoles intensifs dans un environnement riche en ressources (niveaux de rayonnement élevés, sols relativement fertiles, profonds et bien drainés), combinés au transfert de technologie et au renforcement des capacités, pourraient être considérés comme des stratégies viables pour assurer la nourriture des petits agriculteurs et des communautés rurales africaines, tout en améliorant l'utilisation de l'eau dans les bassins hydrographiques. Copyright © 2018 John Wiley & Sons, Ltd.